COMMUNITY BASED TOURISM DI KAWASAN PARIWISATA TANJUNG DURIAT, WADUK JATIGEDE - Siti Komariah; Wilodati Wilodati; Nindita Fajria Utami (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Jatigede reservoir has potential as a tourism destination, this area is intended to be a special economic zone. The purpose of this study is to find Tourist Attractions, Community Based Tourism and SWOT analysis in Tanjung Duriat tourism area, Jatigede reservoir. The method in this study uses as qualitative approach with a case study method. From the results of the study, it was found that there was sufficient Community Based Tourism and a Tourist Attraction.